The Effectiveness of Video-Based Education on the Knowledge of Oral Health Maintenance and Tooth-Brushing Behavior Among the Students of the STM IX in Lurah Jambi - Boy, Hendry; Asio, Asio; Mahendra, Yusri (Sekolah Tinggi Ilmu Kesehatan Harapan Ibu Jambi, 2023)
Adolescents are one of the groups with health problems. Based on the results of the Basic Health Research of the Ministry of Health (Riskesdas) in 2018, based on the presence of dental and oral health problems in the age group 15-24 (51.9%) and only those handled by health workers (8.7%), the data also shows, The prevalence of caries in the age group 15-24 years was (75.3%) with caries and (61.1%) with root caries. Video-based counseling can increase students' knowledge of dental and oral health maintenance. This study aimed to determine the effectiveness of video media on dental and oral health knowledge and tooth brushing behavior in students of STM IX Lurah Jambi in 2022.The type of research was Quasi-Experimental with a one-group pre-test and post-test design—research measuring instrument using a questionnaire. The sample is class XI STM IX Lurah Jambi. The sampling technique used the total sampling method with the number of respondents 20 people. This study uses the paired t-test hypothesis test.The results showed that the level of knowledge of dental and oral health maintenance before counseling had low criteria (10%), moderate (80%), and (10%) high, and after counseling had high criteria (100%). At the same time, the level of tooth brushing behavior before counseling had low criteria. (5%), moderate (85%) and (10%) high, and after counseling, the criteria were high (100%). There is a significant difference between the level of knowledge of dental and oral health maintenance and tooth brushing behavior before and after being given counseling using video media with a p-value of 0.001 (p < 0.05). Keywords: Video, Knowledge, Behavior, Brushing teeth